Corticostriatal Dysfunction in Huntington’s Disease: The Basics - Bunner, Kendra D.; Rebec, George V. (Frontiers in Human Neuroscience, 2016)
The main input to the basal ganglia, the corticostriatal pathway, shows some of the earliest signs of neuropathology in Huntington’s disease (HD), an inherited neurodegenerative condition that typically strikes in mid-life with progressively deteriorating cognitive, emotional, and motor symptoms. Although an effective treatment remains elusive, research on transgenic animal models has implicated dysregulation of glutamate (Glu), the excitatory amino acid released by corticostriatal neurons, in HD onset. Abnormalities in the control of Glu transmission at the level of postsynaptic receptors and Glu transport proteins play a critical role in the loss of information flow through downstream circuits that set the stage for the HD behavioral phenotype. Parallel but less-well characterized changes in dopamine (DA), a key modulator of Glu activation, ensure further deficits in neuronal communication throughout the basal ganglia. Continued analysis of corticostriatal Glu transmission and its modulation by DA, including analysis at the neurobehavioral level in transgenic models, is likely to be an effective strategy in the pursuit of HD therapeutics.